Chemical Composition and Antioxidant Activity of Six Allium Extracts Using Protein-Based Biomimetic Methods - Ioana Andreea Barbu; Vlad Alexandru Toma; Augustin Cătălin Moț; Ana-Maria Vlase; Anca Butiuc-Keul; Marcel Pârvu (MDPI AG, 2024)
Medicinal plants are a valuable reservoir of novel pharmacologically active compounds. ROS and free radicals are primary contributors to oxidative stress, a condition associated with the onset of degenerative diseases such as cancer, coronary heart disease, and vascular disease. In this study, we used different spectrophotometry methods to demonstrate the antioxidant properties of 6 Allium extracts: Allium fistulosum; Allium ursinum; Allium cepa: Arieș red cultivar of A. cepa, and white variety of A. cepa; Allium sativum; and Allium senescens subsp. montanum. HPLC-MS determined the chemical composition of the extracts. Among the tested extracts, the Arieș red cultivar of A. cepa stands out as having the best antioxidant activity, probably due to the high content of polyphenols and alliin (12.67 µg/mL and 3565 ng/mL, respectively). The results obtained in this study show that Allium extracts have antioxidant activity, but also free radical scavenging capabilities. Also, their interactions with cytochrome c and hemoglobin can be the basis of future studies to create treatments for oxidative stress-related diseases.